2021
DOI: 10.1155/2021/6234560
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Traditional Medicine NiuBeiXiaoHe (NBXH) Extracts Have the Function of Antituberculosis and Immune Recovery in BALB/c Mice

Abstract: Background. The Traditional Chinese Medicine NiuBeiXiaoHe (NBXH) is a valid antituberculosis (TB) prescription from the experience of clinical practice. However, the mechanism of NBXH extracts’ immunotherapy has been poorly understood. Herein, the immunotherapeutic efficacy and the differentially expressed (DE) genes of NBXH extracts were evaluated and identified in BALB/c mice. Methods. The total RNA was extracted from peripheral blood mononuclear cells, and the DE genes were identified by gene chip. The enri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Our previous research and other large amounts of data show that TB is not only an infectious disease but also an immune disease (Gong et al, 2018(Gong et al, , 2021Li et al, 2020;Liang et al, 2021;Rambaran et al, 2021). The pathogenesis of TB is closely related to the host's immune response.…”
Section: Novel Biomarkers Derived From Hostsmentioning
confidence: 92%
“…Our previous research and other large amounts of data show that TB is not only an infectious disease but also an immune disease (Gong et al, 2018(Gong et al, , 2021Li et al, 2020;Liang et al, 2021;Rambaran et al, 2021). The pathogenesis of TB is closely related to the host's immune response.…”
Section: Novel Biomarkers Derived From Hostsmentioning
confidence: 92%
“…The imbalance between Mycobacterium tuberculosis invasiveness and host immunity is key to the progression of latent tuberculosis infection (LTBI) into active TB. 3 , 4 , 26 , 30 , 31 Recently, a meta-analysis based on 14 studies involving 22, 616, and 623 participants showed that DM in patients with TB is a significantly increased risk factor that can be reduced by improving glycemic control. 32 …”
Section: Discussionmentioning
confidence: 99%